Class Action Research Workshop With Participant Active Learning for Educators in Gugus 04 Primary School Level Ciputat District – South Tangerang City - Tjipto Djuhartono; Prasetio Ari Wibowo; Haryanto Haryanto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The primary issue identified in this particular service is to the inadequate proficiency of teachers in conducting and documenting Classroom Action Research (PTK) within Cluster 04 Elementary School Level, situated in Ciputat District, South Tangerang City. The objective of this community service initiative is to facilitate the dissemination of information and deliver training on the process of conducting Classroom Action Research in relation to the challenges encountered by teachers and educational personnel in both classroom and non-classroom settings. The program was conducted as a workshop aimed at fostering the development of Bimtek instruments and implementing private Classroom Action Research (PTK) Technical Guidance. It took place on Wednesday, June 21, 2023, at Gugus 04 Elementary School Level, located in Ciputat District, South Tangerang City. The findings of the Abdimas initiatives conducted as teacher aides demonstrate that reflective activities can effectively facilitate learning.